The Emerging Widespread Debris Flow Disasters in Tropical Terrain of Peninsular Malaysia: Understanding the Risk and Policy Intervention - Jaapar A.R.; Md Aripin M.F.S.; Komoo I.; Ali C.A.; Ramli Z.; Harun A.R.; Bachat J.; Mohamad Z.; Omar R.C.; Razak K.A.; Lim C.S. (EDP Sciences, 2024)
Several widespread debris flow disasters stroke Peninsular Malaysia in between 2021 and 2022, scattered across the country. It was the first time for this hazard being nationally recognised as a type of geological disaster in the country. Debris flow disaster is not a new phenomenon. It had been recorded since 1995, however, in the past they were isolated incidents and did not attract much attention. The recent widespread debris flow disasters started in Gunung Jerai, Kedah on 18 August 2021